Subcutaneous Administration of Bortezomib in Combination with Thalidomide and Dexamethasone for Treatment of Newly Diagnosed Multiple Myeloma Patients - Wu, Shenghao (Biomed Res Int, 2015)
Objective. To investigate the efficacy and safety of the treatment of the newly diagnosed multiple myeloma (MM) patients with the therapy of subcutaneous (subQ) administration of bortezomib and dexamethasone plus thalidomide (VTD) regimen. Methods. A total of 60 newly diagnosed MM patients were analyzed. 30 patients received improved VTD regimen (improved VTD group) with the subQ injection of bortezomib and the other 30 patients received conventional VTD regimen (VTD group).The efficacy and safety of two groups were analyzed retrospectively. Results. The overall remission (OR) after eight cycles of treatment was 73.3% in the VTD group and 76.7% in the improved VTD group (P > 0.05). No significant differences in time to 1-year estimate of overall survival (72% versus 75%, P = 0.848) and progression-free survival (median 22 months versus 25 months; P = 0.725) between two groups. The main toxicities related to therapy were leukopenia, neutropenia, thrombocytopenia, asthenia, fatigue, and renal and urinary disorders. Grade 3 and higher adverse events were significantly less common in the improved VTD group (50%) than VTD group (80%, P = 0.015). Conclusions. The improved VTD regimen by changing bortezomib from intravenous administration to subcutaneous injection has noninferior efficacy to standard VTD regimen, with an improved safety profile and reduced adverse events.